Maritime Accident and Incident Investigation - Olsen, Alexander Arnfinn (Routledge, 2024)
Maritime Accident and Incident Investigation covers a wide range of topics relating to maritime-orientated organisational hazards and risks, as well as root cause analyses and techniques for analysing evidence. Its approach to maritime casualty and incident investigation caters to the unique needs of the maritime industry and covers the human element, machinery and engineering, and structural and security concerns. The book is divided into four parts, which respectively introduce the concepts and theories of organisational risks and hazards; provide a framework structure for planning, initiating, performing, and closing out maritime casualty and incident investigations; provide an overview of the main forms of analyses; and offer a toolkit of forms and documents for preparing and carrying out incident investigations.